Vines of the sweet potato (Ipomea batatas): A valuable feed supplement for ruminants in small holder systems - Goopy, John P.; Gakige, J.; Korir, Daniel; Kvacic, M.; Butterbach-Bahl, Klaus (2015)
Availability of suitable feed, and in particular sources of protein-rich food, is a major constraint to increasing the productivity of smallholders in sub-Saharan Africa it is difficult to justify diverting land from growing crops for human consumption. The roots of the sweet potato are a high energy cash crop, and the leaves and vines (SPV), usually treated as rubbish, are high in protein and have been identified as a valuable livestock feed.